METODE PEMBELAJARAN BERBASIS WEB (E-LEARNING) DALAM PROSES BELAJAR MENGAJAR SECARA VIRTUAL - Yanti Fauziah (Jurnal Terapung : Ilmu - Ilmu Sosial, 2020)
Web-based learning which is popularly known as Web-Based Education (WBE) or sometimes called e-learning (electronic learning) can be defined as the application of web technology in the world of learning for an educational process. In simple terms it can be said that all learning is carried out by utilizing internet technology and as long as the learning process is felt by those who follow it, this activity can be called web-based learning. Currently the learning paradigm has changed from teacher-centered learning to student-centered learning, which is characterized by the activeness of learners in the learning process, and it is assumed that learners have responsibility for their own learning activities. Face-to-face traditional learning relates to classroom learning that considers the teacher to be the expert, the main messenger, and the only assessment of learning activities